Kehidupan Spiritual Lansia di Lembaga Sosial Cinta Ibu Tresna Werdha di Nagari Cubadak Kabupaten Lima Kaum Batu - Zunnuraini, Rezni; Afrinaldi, Afrinaldi; M, Iswantir; Yarni, Linda (Lembaga Yasin AlSys, 2023)
This research departs from the theory which suggests that religious spirituality increases in the elderly, namely by increasing religious activities and activities, such as participating in recitations. Apart from preparing themselves to face death, this is also done by the elderly to discover the meaning and importance of life. According to Danah Zohar and Ian Marshall, spiritual comes from the Latin word Spiritus which means something that gives life or vitality to a system. Spiritual religion as one of the foundations that must be owned by every human being in order to make the soul as an insanul kamil in the context of life in accordance with the shari'ah that has been determined by Allah SWT so that the soul is maintained in a state of nature and purity. While what is meant by old age is the age that is approaching the end of the human life cycle in the world. Age in this stage starts from the 60's until the end of life. This stage where aging and decline occur in the form of cumulative changes in living things, including the body, tissues and cells that experience a decrease in capacity.This research was conducted through a qualitative descriptive method, namely a method that gives a systematic description of the situation that occurred in the field. The key informants are the elderly who are in PSTWKSI, and the supporting informants in this study are elderly caregivers. In collecting the data needed, the authors carried out interviews with key informants and supporting informants, as well as to corroborate statements from informants, the authors also made observations. Then the data that has been obtained will be processed using descriptive analysis techniques.Based on the results of this study, it was found how the religious spiritual life of the elderly in the aspects of obligatory and sunnah observance of elderly worship performed together (in congregation) or alone is quite good. Discipline of the elderly in doing the tasks that have been set or by doing it because of their own desires is also quite good. The honesty of the elderly to the people around them is not good, such as to their friends or to caregivers. And the caring attitude towards the elderly in PSTWKSI is quite good.